Ascending: An exploration of women's leadership advancement in the role of board of trustee chair - Heather Inez Ricks Scott (Administrative Sciences, 2018)
While women have made strides in leadership in the higher education sector there continues to be dismal representation of women in executive level roles of governance at colleges and universities. This article presents findings from a study that explored skills that women have identified as being useful in their ascent to the role of trustee board chair. The ascension patterns of the participants are explored through a qualitative process to provide a path to success for other women to follow. The article concludes with suggestions for increasing the number of women serving in the capacity of board chair.
Keywords: 350; women and higher education; leadership; governing boards